The development of the metacognitive thinking skills scale - Tuncer, Murat; Kaysi, Feyzi (My University, 2013)
It is observed that majority of recent studies on cognitive learning are dealing with metacognition. Metacognition is used to follow and regulate cognitive processes such as learning, problem solving, comprehension, reasoning and memory. Therefore, it is possible to gather all information about a problem encountered by the individuals, including its solution, comprehension of its outline or essence and reasoning for solving it. Individuals’ development of metacognitive thinking skills will allow them to act more efficiently in their professions. In this research, a scale was developed in order to measure these metacognitive thinking skills. The scale was proved valid and reliable through employment of exploratory and confirmatory factor analysis.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Metacognition; Learning; Scale development; Metacognitive thinking